Electromagnetic acoustic transducer ultrasonic inspection of additive manufacturing samples - Zu Nurain Bin Mohamad Mudrika (Nanyang Technological University, 2024)
Additive manufacturing has been a very popular choice in manufacturing metallic products in recent years due to its ability to construct products with intricate shapes, while also reducing material wastage. To ensure consistency in quality of these products, comprehensive and accurate inspections are essential to detect any possible defects or anomalies. Inspections are preferably done with non-destructive and non-contact methods to prevent any possible damages during the process. The use of Electromagnetic Acoustic Transducers (EMAT) on post-processed additive manufacturing products can be a valuable approach when facing the constraints and characteristics of such products due to its non-contact method which is effective when applied onto complex geometries or any defects. It is especially useful when inspecting on product surfaces where using conventional ultrasonic inspection might not be suitable for such cases. This report explores the performance of EMAT on metallic materials and samples that underwent additive manufacturing. With the help of coding and automation of a robot arm, accurate data is achieved to collate and present findings such as ultrasonic wave strengths and defects inspection. The findings gathered in experiments also present insightful information regarding the capabilities and reliability of EMAT under various metals and on defective samples.